2020
DOI: 10.3389/fped.2020.00412
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Dynamic Functional Connectivity Associated With Maturity in Late Preterm Infants

Abstract: Objective: To investigate the changes of dynamic functional connectivity (DFC) in late preterm infants, and assess whether these changes are associated with the indicators measuring the maturity of neonates. Methods: Resting-state fMRI (rs-fMRI) data of eligible neonates was acquired with a 3.0-T MRI scanner in the Department of Radiology, Daping Hospital, Army Medical University (Chongqing, China). After the selection of functional connectivity networks obtained by independent component analysis (ICA), a slid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 65 publications
(64 reference statements)
1
5
0
Order By: Relevance
“…We observed that in newborn infants, whole-brain synchrony state A had the highest mean synchronisation, as well as largest fractional occupancy and dwelling times; thus suggesting that newborn infants spend a large amount of their time in a state of global phase synchrony which is a similar to the previously described dominant pattern of whole-brain synchronisation seen with both fMRI (Ma et al, 2020;Wen et al, 2020) and EEG (Tokariev et al, 2019). Together with prior studies, our work supports the idea that large scale activity plays a crucial role in early brain development.…”
Section: Modular Brain State Profile In Term-born Neonatessupporting
confidence: 80%
See 3 more Smart Citations
“…We observed that in newborn infants, whole-brain synchrony state A had the highest mean synchronisation, as well as largest fractional occupancy and dwelling times; thus suggesting that newborn infants spend a large amount of their time in a state of global phase synchrony which is a similar to the previously described dominant pattern of whole-brain synchronisation seen with both fMRI (Ma et al, 2020;Wen et al, 2020) and EEG (Tokariev et al, 2019). Together with prior studies, our work supports the idea that large scale activity plays a crucial role in early brain development.…”
Section: Modular Brain State Profile In Term-born Neonatessupporting
confidence: 80%
“…This adds confidence to the results reported in earlier preliminary studies of dynamic FC in neonates around birth. For example, Ma et al, 2020, described dynamic functional connectivity with four brain states that encompassed default-mode, dorsal attention, auditory, sensory-motor, and visual networks in 37 term neonates (Ma et al, 2020). Here we establish a series of six brain states and describe associations with age at scan and postnatal days in a larger cohort with 324 term neonates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Age‐related differences in FC are evident in the early developmental phase of the brain, with significant rewiring and topological restructuring over time (Fair et al, 2007 ; Power et al, 2010 ; Supekar et al, 2009 ). Existing time‐resolved brain connectivity research in infants, children, and adolescents has shown that the dynamic interregional interactions accurately reflect neonatal maturity (Ma et al, 2020 ), predict brain maturity (Qin et al, 2015 ), present marked changes (Faghiri et al, 2018 ), and variability with maturity (Hutchison & Morton, 2015 ; López‐Vicente et al, 2021 ), differ in atypical development (Liu et al, 2019 ; Rashid et al, 2018 ), characterize risk for neurodevelopment disorders (Marusak et al, 2017 ) and provide unique insights regarding pathophysiology (Sato et al, 2015 ). In contrast, brain connectivity again evolves in middle and late adulthood and is accompanied by gradual cognitive decline.…”
Section: Introductionmentioning
confidence: 99%